Analisis Seni Rupa sebagai Pengembangan Kreativitas dan Ekspresi Diri Siswa Kelas V SD - Hasanah, Radita; Andaryani, Eka Titi (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
Fine arts are a subject that is excluded in elementary schools in terms of class hours and funding. In reality, fine arts help students improve their creativity and self-expression skills. This study aims to analyze fine arts as a medium for developing creativity and self-expression skills of grade V elementary school students at SD N Nongkosawit 02 Semarang, as well as to find out the inhibiting factors and solutions in the development of creativity and self-expression skills of students in fine arts lessons. This type of research is qualitative with a descriptive qualitative approach. Data collection techniques are carried out by non-test methods in the form of interviews, questionnaires, documentation, and observations. The data analysis technique uses data triangulation and the Likert scale with the help of Microsoft Excel. The results of this study are 10 students in class V. The results of this study are effective in developing creativity and self-expression skills of class V students seen from the data of the score above the KKM and the results of the questionnaire of student self-expression through art learning get an average of 86% (very high), the factors that hinder students' creativity are from external sources in the form of minimal parental support/attention, The solution is more assistance from parents to students, the school held a meeting of the parents' association which was accompanied by an exhibition of students' fine art. For other factors, such as incomplete learning facilities, the solution is that schools hold school cooperatives, look for partners with local artists or art communities for donated tools or materials, develop art curricula, and utilize digital technology. Hopefully, this research will be helpful for other researchers, especially for fine arts learning, especially the emphasis on creativity and students' self-expression skills.